Fortune or fortitude? Determinants of successful adjustment with IMF programs - Larch, Martin (OECD Publishing, 2017)
Full adjustment programs in the wake of crisis episodes exact a major toll on a country's economy, yet not all are blessed with success.We identify adjustment needs by a country's decision to approach the IMF for official assistance.We then investigate the factors conducive to successful exit from official assistance during more than 170 adjustment episodes by means of a panel regression framework. In contrast to the existing literature, we do not use absolute benchmarks. We define success as a resumption of real GDP growth and a reduction of government debt compared to the pre-program period. Our econometric results suggest stringent policy action do play a role for the probability of success. At the same time, we also find that successful exit also very much depends on supportive external conditions and, linked to that, the degree of openness of an economy. JEL classification: E61, F33, G01, H81 Keywords: Fiscal adjustment, financial crises, IMF lending